Fieldwork in Ecclesial Borderlands: Culture, Community, and Belonging in a Multiethnic Boston Parish - Reynolds, Susan Bigelow (Exchange, 2019)
Roman Catholic parishes in the United States are steadily becoming more diverse. This article examines St. Mary of the Angels, a small, urban, economically marginal, highly diverse Roman Catholic parish in Boston, as a case study in the question of how researchers might approach the tension between cultural dynamism and structural stability at the heart of multiethnic parish life. Attending to the ways in which parishioners articulated their decisions to belong to St. Mary's, I demonstrate how their renegotiation of the relationship between parish, place, and belonging reflects broader dynamics underway in U.S. Catholicism. I propose the metaphor of the ecclesial borderland as lens through which to interpret parishes where multiple cultural subcommunities coexist and converge.